IMPLEMENTASI MODEL PEMBELAJARAN TPACK (TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE) PADA MATA PELAJARAN PAI MELALUI PLATFORM WORDWALL DI SMPN 35 SURABAYA - Mahbubatul Khoiriyah; Mas’ady Ashabul Kahfi; Muhammad Fahmi; Syaifuddin Syaifuddin (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
This study aims to analyze the implementation of the Technological Pedagogical and Content Knowledge (TPACK) learning model through the Wordwall platform in Islamic Religious Education (IRE) learning at SMP Negeri 35 Surabaya. The background of this study stems from the low level of student engagement in IRE learning due to the dominance of conventional methods and the suboptimal integration of technology in the learning process. This study uses a descriptive qualitative approach, with the research subjects consisting of PAI teachers and seventh-grade students. Data were collected through participatory observation, in-depth interviews, documentation studies, and field notes, then analyzed using the interactive model of Miles, Huberman, and Saldana. The results show that the application of the TPACK model through Wordwall successfully increased student engagement and motivation to learn. Careful planning, the use of Wordwall's interactive features (such as quizzes, matching games, and random wheels), and collaborative pedagogical strategies created an active, enjoyable, and meaningful learning atmosphere. Despite challenges such as time constraints, digital infrastructure, and variations in students' technological literacy, teachers were able to overcome them through adaptive strategies such as hybrid learning, group role rotation, and collaborative reflection. This study confirms that integrating the TPACK model through Wordwall can be an innovative strategy for transforming PAI learning into interactive, contextual learning that is in line with the principles of the Merdeka Curriculum.